Perceived cultural ecosystem services in Zaribar Coastal Park: Implications for tourist well-being - Arman Rastkhadiv; Aisa Fouladi; Jafar Bapiri (Journal of the Bulgarian Geographical Society)
Cultural ecosystem services embedded in urban green spaces play a vital yet often underappreciated role in shaping tourists’ well-being. This study investigates the perceived contributions of cultural ecosystem services to tourist well-being in Zaribar Coastal Park, a multifunctional urban green space located in Kurdistan Province, Iran. Drawing on the Millennium Ecosystem Assessment framework, ten cultural ecosystem services dimensions were examined through a structured survey of 300 domestic tourists. The sample was selected via Mitra and Lankford’s method, and data were analyzed using partial least squares structural equation modeling. Findings reveal that outdoor recreation, aesthetic appreciation, social relations, cultural heritage, educational values, and sense of place significantly enhance tourists’ well-being, while cultural diversity, inspiration, knowledge systems, and spiritual values exerted limited or statistically insignificant effects. This study advances theoretical understanding by refining the cultural ecosystem services–well-being linkage within urban tourism contexts and demonstrating the contextual specificity of cultural ecosystem services impacts. Practically, the findings underscore the need for tourism planners and policymakers to integrate cultural ecosystem services into destination design and management strategies. Prioritizing experiential, aesthetic, and recreational dimensions of cultural ecosystem services can foster more inclusive, sustainable, and human-centered urban tourism models.